Potentiation of Glutamatergic Synaptic Transmission Onto Dorsal Raphe Serotonergic Neurons in the Valproic Acid Model of Autism - Wang, Ruixiang; Hausknecht, Kathryn; Shen, Roh-Yu; Haj-Dahmane, Samir (Frontiers in Pharmacology, 2018)
Autism spectrum disorder (ASD) is characterized by social and communicative impairments and increased repetitive behaviors. These symptoms are often comorbid with increased anxiety. Prenatal exposure to valproic acid (VPA), an anti-seizure and mood stabilizer medication, is a major environmental risk factor of ASD. Given the important role of the serotonergic (5-HT) system in anxiety, we examined the impact of prenatal VPA exposure on the function of dorsal raphe nucleus (DRn) 5-HT neurons. We found that male rats prenatally exposed to VPA exhibited increased anxiety-like behaviors revealed by a decreased time spent on the open arms of the elevated plus maze. Prenatal VPA exposed rats also exhibited a stereotypic behavior as indicated by excessive self-grooming in a novel environment. These behavioral phenotypes were associated with increased electrical activity of putative DRn 5-HT neurons recorded in vitro. Examination of underlying mechanisms revealed that prenatal VPA exposure increased excitation/inhibition ratio in synapses onto these neurons. The effect was mainly mediated by enhanced glutamate but not GABA release. We found reduced paired-pulse ratio (PPR) of evoked excitatory postsynaptic currents (EPSCs) and increased frequency but not amplitude of miniature EPSCs in VPA exposed rats. On the other hand, presynaptic GABA release did not change in VPA exposed rats, as the PPR of evoked inhibitory postsynaptic currents was unaltered. Furthermore, the spike-timing-dependent long-term potentiation at the glutamatergic synapses was occluded, indicating glutamatergic synaptic transmission is maximized. Lastly, VPA exposure did not alter the intrinsic membrane properties of DRn 5-HT neurons. Taken together, these results indicate that prenatal VPA exposure profoundly enhances glutamatergic synaptic transmission in the DRn and increases spontaneous firing in DRn 5-HT neurons, which could lead to increased serotonergic tone and underlie the increased anxiety and stereotypy after prenatal VPA exposure.